Risk factors associated with neonatal thrombocytopenia in pregnant women with immune thrombocytopenic purpura. (2nd May 2020) - Rottenstreich, Amihai; Israeli, Noa; Roth, Batia; Elchalal, Uriel; Amsalem, Hagai; Da'as, Nael; Rottenstreich, Misgav; Kalish, Yosef
Abstract: Objectives: To characterize the risk factors associated with neonatal thrombocytopenia among pregnant women with immune thrombocytopenic purpura (ITP). Methods: We reviewed the records of ITP patients who delivered during 2006–2016 at our medical center. Results: Of 253 pregnancies, median maternal age at diagnosis was 29 [25–33] years, 222 (87.7%) had previously-diagnosed ITP and 31 (12.3%) were diagnosed with new-onset ITP during pregnancy. Baseline characteristics were comparable between the groups except for a higher proportion of nulliparity among those with new-onset disease ( p  = .002). Maternal nadir platelet count was significantly lower among those with new-onset compared to previously diagnosed ITP (median 62 × 10 9 /L versus 81 × 10 9 /L, p  = .005). Neonatal thrombocytopenia (<150 × 10 9 /L) was encountered in 24 (9.5%) pregnancies and required treatment in 12 (50%) of them. Neonatal platelet count was directly correlated with maternal platelet count at delivery ( r  = 0.23, p  = .01), with significantly lower maternal platelet count among those whose newborns experienced thrombocytopenia ( p  < .001). Neonatal thrombocytopenia followed a higher proportion of pregnancies of women with new-onset than previously diagnosed ITP (22.6 versus 7.7%, p  = .02). In multivariate analysis, the presence of new-onset ITP (odds ratio [95% CI]: 4.88 (1.68, 14.16), p  = .004) was the only independent predictor of the development of neonatal thrombocytopenia. Conclusion: Neonatal thrombocytopenia presented following almost one-tenth of pregnancies with ITP. New pregnancy-onset disease was the only prognostic marker for neonatal thrombocytopenia. This finding could contribute to risk stratification and individualized patient management.